THE ROLE OF SERVICE QUALITY IMPROVES BRAND IMAGE IN HOTELS XYZ: WORD OF MOUTH AS A MEDIATION - MH Nainggolan, Bonifasius; Amidiola, Puan (Journal of Management and Leadership, 2021)
This study aims to analyze the effect of service quality on the brand image through word of mouth at Hotel XYZ Jakarta. The population in this study were all guests who came to the Hotel XYZ Jakarta, using primary data obtained from questionnaires with the accidental sampling method. Data samples were obtained from 234 respondents at Hotel XYZ in Jakarta. This study uses non-probability sampling with the SEM method, which is processed by SPSS and SmartPLS programs. The results represent service quality has a direct influence on word of mouth and brand image. Word of mouth also directly influences the brand image and can mediate the relationship between service quality and brand image.